The Cartographic representation of Climate Elements in the area of Misrata By Using Geographical Information Systems (Journal of Libya for geographical studies, 2022)
The research aims to represent the elements of the climate in Misrata region cartographically, where there are many methods of distributing climatic elements on maps in GIS programs. The study was limited to the use of the spacing method by using readable equality lines, in the presentation of available climate data, relying on color and line variables to highlight the variation in the rates and distribution of the climate element, through GIS programmes using spatial completion tools. The study came to the conclusion that arc GIS10.3's have high potentials for cartographically depicting climate elements using the Spline slide method, which is one of the most important and efficient ways to complete, represent and map annual climate data accurately; furthermore, there is shown a disparity in the distribution of climate elements rates at Misrata stations.
Keywords: The Cartographic representation; Climate Maps; Geographic information systems; Spatial Interpolation